Neurocognitive functioning in the premorbid stage and in the first episode of bipolar disorder: A systematic review - Martino, Diego Javier (2015)
It is well known that patients with bipolar disorder (BD) have cognitive impairments even during periods of euthymia. However, to date it remains unclear the moment when these deficits onset. Therefore, the aim of this study was to review the evidence focusing on the cognitive status of patients with BD in their premorbid stage and in their first episode. An extensive search was conducted through the online databases Pubmed/PsychInfo, covering the period between 1980 and 2014. A total of 23 studies were selected for the review (nine studies explored premorbid stage of people who lately develop BD and 14 examined first-episodes in bipolar patients). There is evidence that general intelligence is not impaired in the premorbid stage. Impairments in verbal memory, attention, and executive functions tend to be present during and after the first episode. Preliminary evidence suggests that these deficits in specific cognitive domains might precede the onset of illness.